Annual ADEA Survey of Dental School Seniors: 2016 Graduating Class. Issue 5 (1st May 2017) - Wanchek, Tanya; Cook, Bryan J.; Valachovic, Richard W.
Abstract : This report examines the results of the American Dental Education Association (ADEA) Survey of Dental School Seniors graduating in 2016. Data were collected from 4, 558 respondents at all 59 U.S. dental schools with graduating classes that year. This annual survey asks graduating students about a variety of topics in order to understand their motivation for attending dental school, educational experiences while in school, debt incurred, and plans following graduation. Motivations for choosing to attend dental school typically involved family or friends who were dentists or students' personal experiences. The timing of the decision to enter dentistry has been getting earlier over time. Similar to previous years, the average graduating student had above $200, 000 in student debt. However, for the first time in two decades, inflation‐adjusted debt decreased slightly. The reduction in debt was due to students from private schools reducing their average debt by $23, 401. Immediately after graduation, most seniors planned to enter private practice (50.5%) or advanced dental education (33.8%). Approximately half of the respondents planned to work in underserved areas at some point in their careers. These findings underscore the continued value of the senior survey to offer a unique view of the diverse characteristics and career paths of the future dental workforce.